PEMBERIAN BANTUAN HUKUM BAGI TERDAKWA MASYARAKAT MISKIN YANG DIANCAM DENGAN PIDANA KURANG DARI 5 TAHUN - ahmad febrian khoirurizal (MIH Unsoed, 2022)
Legal aid is constitutional rights for every citizen to get guaranteed legal protection and equality before the law. Legal aid in court hearings is an important instrument in the criminal justice system because it is part of the protection of human rights for every citizen. Legal aid is a right held by a defendant for the purpose of his defense in the criminal justice process. Through the provision of legal aid, it is hoped that fair and impartial criminal justice can be achieved and defendants receive humane treatment. Providing legal assistance is seen as a social responsibility in the context of law enforcement to anyone. Legal aid in a broad sense can be interpreted as an effort to help groups who are less fortunate in the field of law. Based on this, it is interesting to conduct research if it is viewed from the applicable regulations related to its implementation, especially in this research in the Banyumas District Court.The method used in this research is empirical legal research. Sources of data contained in this study come from primary data and secondary and, with data collection techniques based on interviews with informants and literature study. The data analysis technique in this study uses the deductive method.Based on the results of this study, it is known that the law enforcement components such as judges and lawyers / law enforcers have implemented it according to the mandate of the laws and regulations. However, because in essence legal aid is the right of the Defendant, it is an option for the Defendant to be accompanied by a Legal Counsel or not through access to legal assistance. In the case that what the defendant experiences is a criminal threat of more than 5 years, the Legal Aid Post (Posbakum) can be a means of obtaining free legal assistance and this facility is already available in every court, especially the Banyumas District Court. The obstacles that were often faced were precisely the Defendants whose criminal threats were under 5 years, because the Defendants lacked knowledge and information, as well as difficult access to administrative requirements in the form of SKTM, made the Defendants reluctant to choose to be accompanied by a Legal Counsel through legal aid. Meanwhile, on the other hand, from the law enforcement component such as Judges or Advocates, because Defendants who are sentenced to under 5 years of punishment are not obliged to be assisted by a Legal Counsel, this means that there is no direct approach to the Defendant regarding their right to obtain legal assistance. in the form of assistance or legal advisors to defend their rights and interests in court.